Degradation of congo red dye in aqueous solution by using advanced oxidation processes / Alya Nadhira Nasron... [et al.] - Nasron, Alya Nadhira; Azman, Ninna Sakina; Mohd Rashid, Nor Syaidatul Syafiqah; Said, Nur Rahimah (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Degradation of azo dyes by using advanced oxidation processes (AOPs) was conducted. In this approach, different AOPs, which are Fenton process and titanium dioxide (TiO 2 ) catalyst, were examined and compared for the degradation of an azo dye (i.e., Congo red dye). The sample was tested under UV light and the experiment was conducted for 90 min with 15 min interval. The degradation rate of dye was determined using UV-Vis spectrophotometry. The effect of several parameters on the degradation process such as the concentration of metal ions (Fe 2+ , Cu 2+ , and Mn 2+ ) as the catalyst in Fenton process, the concentration of hydrogen peroxide (H 2 O 2 ), the mass of TiO 2 , and pH value of the dye solution were investigated. The initial Congo red concentration used for both techniques was 5 ppm. The results showed that the percentage degradation followed the sequence of H 2 O 2 /Fe 2+ /UV, H 2 O 2 /Cu 2+ /UV, H 2 O 2 /Mn 2+ /UV, and TiO 2 /UV. The best operating conditions for H 2 O 2 /Fe 2+ /UV were pH 3, 0.2 M concentration of H 2 O 2 , and 0.02 M concentration of metal ion in 15 min, which achieved 99.92% degradation of dye. The Fourier transform infrared (FTIR) spectrum showed the absence of azo bond (N=N) peak after degradation process, which indicates the successful cleavage of azo bond in the chemical structure of Congo red.